2021
DOI: 10.1002/cbin.11597
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in the regulation of p53‐mediated apoptosis in human cancers

Abstract: Long noncoding RNAs (lncRNAs) are widely known for their regulatory function in transcriptional and posttranscriptional processes. The involvement of such non‐protein‐coding RNAs in nuclear organization and chromatin remodeling is often associated with an increased risk of human malignancies. In cancer, lncRNAs either promote cell survival or may act as a growth suppressor, thus conferring a key regulatory function other than their established role in fundamental cellular processes. Interestingly, lncRNAs inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 140 publications
0
6
0
1
Order By: Relevance
“…The drug‐treated cells acquire activated damage repair mechanism, therefore, harbor functional p53 to promote cell‐cycle arrest (Upadhyay etl., 2016; Toma‐Jonik et al, 2019). Interestingly, the tumor suppressing or tumor driving lncRNAs regulate (regulators) or are regulated (effectors) by p53 to control transcriptional activity of genes involved in cell‐cycle arrest and apoptosis (Sanchez Calle et al, 2018, reviewed in Chatterjee & Viswanathan, 2021). It is tempting to demonstrate that in cancer cells SatIII colocalizes with p53 during the formation of nSBs.…”
Section: Discussionmentioning
confidence: 99%
“…The drug‐treated cells acquire activated damage repair mechanism, therefore, harbor functional p53 to promote cell‐cycle arrest (Upadhyay etl., 2016; Toma‐Jonik et al, 2019). Interestingly, the tumor suppressing or tumor driving lncRNAs regulate (regulators) or are regulated (effectors) by p53 to control transcriptional activity of genes involved in cell‐cycle arrest and apoptosis (Sanchez Calle et al, 2018, reviewed in Chatterjee & Viswanathan, 2021). It is tempting to demonstrate that in cancer cells SatIII colocalizes with p53 during the formation of nSBs.…”
Section: Discussionmentioning
confidence: 99%
“…p53 mutant has designated as a gain-ofoncogenic function(s) (GOFs) which improved cell migration, proliferation, as well as invasion with anti-apoptotic functions which dynamically contribute to numerous phases of tumor progression in cancer (Dittmer et al, 1993;Oren and Rotter, 2010). The changes beyond cancerous are subjected to deliberate discriminating benefits such as facilitating angiogenesis, continuous growth avoiding growth signal, insensitivity to cancer drugs, promotes adequate metabolism, escape from apoptosis with the self-sufficiency of stress signal and ultimately promoting metastasize and invasion (Chatterjee and Viswanathan, 2021;Hernandez Borrero and El-Deiry, 2021). Furthermore, growing evidences from in vitro and in vivo have signified that the oncogenic activities of p53 mutant variants have heterogeneous which can vary with tissue type in addition to genetic background of the cells (Eriksson et al, 2017).…”
Section: Role Of Mutant P53 Contributes To Autophagy Regulation In Cancermentioning
confidence: 99%
“…Increasing evidence has shown that the mutational status and the functional regulation of TP53 in cancers are related to the disordered expression of lncRNAs directly or indirectly ( Aubrey et al, 2018 ). TP53, is considered the “guardian of the genome” and triggers cell apoptosis by inhibiting multiple pathways, and participates in the identification of DNA damage via DNA repair processes, thereby playing an important role in maintaining genomic stability ( Chatterjee and Viswanathan 2021 ). In other words, disrupting the “guardian of the genome” could force damaged cells into senescence or apoptosis, thereby accelerating the accumulation of somatic mutations.…”
Section: Discussionmentioning
confidence: 99%